RIG-I detects viral genomic RNA during negative-strand RNA virus infection. - Rehwinkel, J; Tan, C; Goubau, D; Schulz, O; Pichlmair, A; Bier, K; Robb, N; Vreede, F; Barclay, W; Fodor, E; Reis e Sousa, C (2010)
RIG-I is a key mediator of antiviral immunity, able to couple detection of infection by RNA viruses to the induction of interferons. Natural RIG-I stimulatory RNAs have variously been proposed to correspond to virus genomes, virus replication intermediates, viral transcripts, or self-RNA cleaved by RNase L. However, the relative contribution of each of these RNA species to RIG-I activation and interferon induction in virus-infected cells is not known. Here, we use three approaches to identify physiological RIG-I agonists in cells infected with influenza A virus or Sendai virus. We show that RIG-I agonists are exclusively generated by the process of virus replication and correspond to full-length virus genomes. Therefore, nongenomic viral transcripts, short replication intermediates, and cleaved self-RNA do not contribute substantially to interferon induction in cells infected with these negative strand RNA viruses. Rather, single-stranded RNA viral genomes bearing 5'-triphosphates constitute the natural RIG-I agonists that trigger cell-intrinsic innate immune responses during infection.